Nano-engineering of materials for nonlinear optical imaging - Clays, K; Vanderleyden, J; Anderson, H (2009)
We discuss the use of genetically modified fluorescent proteins (FPs) and a specially engineered chromophore for nonlinear optical imaging. While it is clear that FPs can be used for two-photon fluorescence (TPF) microscopy, we show that they also exhibit a large second-order nonlinear optical response, useful for second-harmonic generation (SHG) imaging. The relation between the linear and nonlinear optical properties in a small series of FPs will be discussed. We also present a new optimized chromophore for combined TPF and SHG microscopy and we show imaging results obtained on this chromophore on a water droplet model system. © 2009 SPIE.